ARUS KAS OPERASI, PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM, KEBIJAKAN DIVIDEN SEBAGAI MODERASI - Abidin, Jaenal; Adi Indrawan, I Gede; Widya Sasana, Lodang Prananta (Jurnal Riset Terapan Akuntansi, 2025)
The share price is the price of a share that occurs on the stock market at a certain time determined by market participants and is determined by the demand and supply of shares in the capital market. Increases and decreases in stock prices are influenced by many factors. This study aims to determine the effect of Operating Cash Flow, Sales Marketing on Stock Prices with Dividend Policy as a Moderating Variable in the Subsector Company industry listed on the Indonesia Stock Exchange in 2017-2021. The sample selection method used purposive sampling method, based on this method obtained 10 companies with 5 years of research, the total research data obtained were 50 observation data. The analysis technique used is panel data regression which is a combination of time series data and cross section data. The results showed that partially operating cash flow had no positive and insignificant effect on stock prices. Sales growth has no positive and insignificant effect on stock prices and dividend policy has a negative and significant effect on stock prices. Dividend Policy does not moderate Operating Cash Flow on Share Price. Dividend Policy does not moderate Sales growth on Share Price. Simultaneously it shows that Operating Cash Flow, Sales Sales and Dividend Policy simultaneously affect the Stock Price. Keywords: Operating Cash Flow, Sales Sales, Dividend Policy, Stock Price